Broker and Market of Resources as Organizational Mechanisms for Sustainability of Resources Selection Processes In Agile / Virtual Enterprises - Ávila, Paulo (2006)
Our Agile / Virtual Enterprises (A/V E) model, it is associated with the creation of temporary net of several physical organizations (or resources), with the intention to develop and produce one or more products/services, in the quantity and quality desirable, answering rapidly to a market solicitation. Our model has to satisfy four functional requirements: virtuality, distributivity, integrability and agility. The main mechanisms, or tools, for assuring satisfaction and implementation of these requirements, by the Virtual Enterprises Architecture Reference Model (BM_VEARM), are the Broker, the Market of Resources and the virtuality (as the specific organization architectural, or structural, pattern). In this paper, Broker and Market of Resources, and their roles and relationship within the process of resources selection, as one of the main processes of the A/V E as well as one of the “agility” processes, are considered. Both of them, Broker and Market of Resources, are independent physical entities, with own juridical identification, that inter-working between them and the Principal (the mentor of a business opportunity), could origin an A/V E creation. We will show in this article the main functions and its organizational position, associated to the triple Broker – Resources Market – Principal, for the A/V E configuration and operation. For the resources system selection those functions will be more detailed explained and identified its tools or type of tools, and its desired performance to assure the A /V E integrability and agility. One of these kinds of tools, are expected to be quality assurance tools, namely the value analyses.